Variability of kinematic and kinetic gait data in ambulatory children with spastic cerebral palsy with and without fixed ankle-foot orthoses using 3d motion analysis: a quantitative prospective study. Issue 2 (20th January 2011) - Mohammed, U; Twycross-Lewis, R; Timotijevic, T; Woledge, R; Bader, D; Paterson, M; Coggings, D; Morrissey, D
Abstract : Background: Spastic cerebral palsy (SCP) is a common neurological disorder causing inadequate motor-control and functional gait pattern. Fixed ankle-foot orthoses (FAFOs) have become a widespread conservative therapy in SCP. Gait of these children exhibits a large degree of within-child variability but few studies have investigated this variability in terms of kinematics and kinetics and no studies address how this variability is affected with the use of FAFOs. Objectives: To compare intrapatient variability of kinematic and kinetic gait parameters between a sample of ambulatory children with SCP and two healthy children with normal gait. The secondary aim was to assess if these variability profiles change in the SCP children as a result of FAFO application. Methods: Four SCP and two normal ambulatory children, aged 5–15, were recruited and underwent active instrumented gait analysis over a 6 week period. Variability of a measure was defined as the SD of the measure within one child over several repeated gait trials. Results: Variability of sagittal-plane pelvic, hip, knee and ankle range of motion (all p<0.01) and sagittal internal hip and knee extensor moments (both p<0.05) were shown to be consistently greater in SCP than that of age-matched children. AFO application reduces sagittal kinematic variability at the pelvis, knee and ankle (all p<0.05) and variability of sagittal hip and knee moments (both p<0.01). Conclusions: Children with SCP exhibit significantly higher kinematic and kinetic variability compared to the normal population. FAFOs have the potential to reduce this variability and functionally improve gait. Future studies should utilise larger sample sizes and stricter inclusion criteria taking into account the differing clinical severities of spasticity, FAFO designs and patterns of CP involvement to ensure these are generalisable findings.